Immune Cell Landscaping Reveals Distinct Immune Signatures of Inflammatory Bowel Disease - Bai, Xiaowu; Liu, Weixin; Chen, Hongxia; Zuo, Tao; Wu, Xiaojian (Frontiers in Immunology, 2022)
Determining how the profile of immune cells varies with their disease subtypes and across lesion locations is critical for understanding the pathogenesis in inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC). To that end, we herein combined the IBD TaMMA framework and the CIBERSORT pipeline to deconvolute the large amount of RNA-seq data from patients with IBD (both CD and UC were included) and healthy human controls across 28 cohorts (a total of 3852 samples) while accommodating data heterogeneity across cohorts, to define the immune cell landscape of IBD. Our study uncovered that both absolute quantities of innate and adaptive immune cell populations were elevated in most intestinal regions of IBD patients, yet disease-specific (CD versus UC) and intestinal location (ileum, colon and rectum)-specific features. In the ileum, the increase of innate immune cells was more pronounced in CD than UC. In contrast, innate and adaptive immune cells were elevated more drastically in the UC than CD, in the rectum. Such revelation of immune signatures across the highly variable IBD phenotypes (in both disease subtypes and intestinal regions) underpins differential immune-pathophysiological mechanisms in IBD pathogenesis and therefore serves as a resource for development of future targeted studies.